Van Wyk Grumbach syndrome with precocious puberty and ovarian cysts: Value of thyroid function tests - Vivek Pant; Suman Baral (Journal of Pediatric Surgery Case Reports, 2019)
Introduction: Van Wyc Grumbach syndrome is a rare presentation of long standing pre-pubertal hypothyroidism characterized by bilateral multicystic ovaries, vaginal bleeding and delayed skeletal growth in case of female. Laboratory investigation reveals very high levels of thyroid stimulating hormone and there is presence of delayed bone growth. Case report: Here, we present a clinical course, diagnosis and management of a case of Van Wyc Grumbach syndrome in a 5 year Nepalese female child who otherwise would have undergone surgical intervention if timely thyroid function test was not done. Conclusion: It is important to recognize this syndrome because prompt initiation of easily available thyroid hormone therapy can completely resolve symptoms, avoiding unnecessary investigations and interventions. Keywords: Ovarian cyst, Hypothyroidism, Van Wyc Grumbach syndrome, Delayed bone growth